Distribution of 10-year and lifetime predicted risk for cardiovascular disease in the Indian Sentinel Surveillance Study population (cross-sectional survey results). Issue 1 (29th April 2011) - Jeemon, Panniyammakal; Prabhakaran, Dorairaj; Huffman, Mark D; Ramakrishnan, Lakshmy; Goenka, Shifalika; Thankappan, K R; Mohan, V; Joshi, Prashant P; Mohan, B V M; Ahmed, F; Ramanathan, Meera; Ahuja, R; et al.
Abstract : Introduction: Cardiovascular disease (CVD) prevention guidelines recommend lifetime risk stratification for primary prevention of CVD, but no such risk stratification has been performed in India to date. Methods: The authors estimated short-term and lifetime predicted CVD risk among 10 054 disease-free, adult Indians in the 20–69-year age group who participated in a nationwide risk factor surveillance study. The study population was then stratified into high short-term (≥10% 10-year risk or diabetes), low short-term (<10%)/high lifetime and low short-term/low lifetime CVD risk groups. Results: The mean age (SD) of the study population (men=63%) was 40.8±10.9 years. High short-term risk for coronary heart disease was prevalent in more than one-fifth of the population (23.5%, 95% CI 22.7 to 24.4). Nearly half of individuals with low short-term predicted risk (48.2%, 95% CI 47.1 to 49.3) had a high predicted lifetime risk for CVD. While the proportion of individuals with all optimal risk factors was 15.3% (95% CI 14.6% to 16.0%), it was 20.6% (95% CI 18.7% to 22.6%) and 8.8% (95% CI 7.7% to 10.5%) in the highest and lowest educational groups, respectively. Conclusion: Approximately one in two men and three in four women in India had low short-term predicted risks for CVD in this national study, based on aggregate risk factor burden. However, two in three men and one in two women had high lifetime predicted risks for CVD, highlighting a key limitation of short-term risk stratification.